Tinjauan Yuridis Pasal 73 Peraturan Pemerintah Nomor 11 Tahun 2021 Tentang BUM Desa : (Analisis Pengelolaan Dana Bergulir Masyarakat Eks Program Nasional Pemberdayaan Masyarakat Eks Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan) (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This research aims to understand and analyze Article 73 of Government Regulation No. 11 of 2021 on Village-Owned Enterprises (BUM Desa) with a focus on the transformation of Community Revolving Funds (DBM) from the former PNPM MPd into BUM Desa bersama LKD). The research discusses the use of DBM assets from the former PNPM MPd as capital in the formation of BUM Desa bersama LKD, as mandated by Article 73 of Government Regulation No. 11 of 2021 on Village-Owned Enterprises. This regulation is in accordance with the mandate of Law No. 6 of 2023 on the Enactment of Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation as a Law and Law No. 3 of 2024 on the Second Amendment to Law No. 6 of 2014 on Villages. The data collection technique used in this research is documentation with an analytical matrix instrument. This study employs a normative juridical legal research method, as the title indicates a juridical review. The research concludes that the management of DBM from the former PNPM MPd must transform into BUM Desa bersama LKD to provide a legal foundation and certainty for DBM activities, ensure the preservation of communal assets in one sub-district, and utilize DBM assets from the former PNPM MPd as capital in the establishment of BUM Desa bersama LKD. The issuance of Government Regulation No. 11 of 2021 on BUM Desa is seen as the government's responsibility in overseeing the management of DBM from the former PNPM MPd as part of poverty alleviation efforts.